A dança na formação de professores de educação física : saberes e conhecimentos na intervenção profissional - Barbosa, Elisangela Almeida (2011)
This research aims to identify which knowledge/skills permeate the development of dance in the process of professional formation of Physical Education in graduate courses in Physical Education presents in the state of Mato Grosso, in the view of teachers responsible for this content at the Universities. The theoretical reference approached the teacher formation process, knowledge and skill mobilized in teaching practice, formation in Physical Education, as well as the knowledge and skill in the area, and concepts and knowledge of dance and its relation to Physical Education. The research is characterized as descriptive, showing a qualitative approach. Dealing with the data came from the interpretive analysis, which allows to put on a larger meaning to the answers. The universe consists of 11 courses in Physical Education into the State of Mato Grosso, which is present in the teaching of dance in specific and related disciplines. The subjects are 12 teachers responsible for teaching dance in these courses. The research instruments were a questionnaire consisting of questions that focused on concepts of Dance, important knowledge about Dance to the professional Physical Education and relationship between Dance and Physical Education, and documentary analysis of the courses programs of all institutions, relating the answers of the subjects. It was identified that 11 teachers have a course in Physical Education and 01 has course in Dance, and 09 of them have expertise in Physical Education, besides the expertise, and 05 are master teacher is in the process of PhD. It was found that 10 teachers had different experiences in Dance, it can contribute to a better understanding of the issues surrounding it. In relation to the concepts of Dance, directed answers to questions related to the expressiveness and emotion movement, nonverbal language, artistic expression and source of knowledge and information. In all concepts is possible to identify the underlying world view expressed by dance movement, which varies according to its historical route and with whom protagonist it. Teachers cited the rhythm, body awareness, historical and cultural contextualization, pedagogical aspects, relation between the theory and practice, formation of concepts and types of dances as important elements in formation. Such answers allow to understand that there is, for some teachers, an understanding and knowledge about the multiple possibilities approach to the dance, which is confirmed in the programs of the courses offered. Few teachers understand to be efficient for learning the way how to dance in the Physical Education course. Difficulties are present in the teaching of Dance in the course, referring to the prejudice on the part of academics, expected technical work by academics and stereotypical images of the Dance, among others. Teachers aim that students apprehend the basic knowledge about Dance, which involves several of its elements to work in school, within the Physical Education, valuing it as a pedagogical tool and as a cultural manifestation through educational practices that awaken attention and interest to the possibilities of experiences provided by a content rich.